Enhancing Innovative Entrepreneurial Behavior of University Alumni MSMEs Owners in Yogyakarta through Entrepreneurship Education, Attitude, Subjective Norms, and Entrepreneurial Intention. - Yuni Mariani Manik; Yuliastuty Puspitaningrum; Siti Amalia (Journal of Economics Education and Entrepreneurship, 2026)
High unemployment among educated youth highlights the need for strengthening entrepreneurial capacity and innovative behavior. Universities and the social environment play a strategic role in shaping entrepreneurial mindsets through learning, attitude development, and social reinforcement. The interplay between entrepreneurial learning, attitude, subjective norms, and entrepreneurial intention provides an important theoretical basis for understanding innovative entrepreneurial behavior. This study aims to analyze the direct and indirect influence of entrepreneurial learning, entrepreneurial attitude, subjective norms, and entrepreneurial intention on innovative entrepreneurial behavior among university alumni MSME owners in Yogyakarta. An explanatory research design with a cross-sectional survey approach was adopted. The population consisted of 270 alumni entrepreneurs, and 135 respondents were selected using purposive proportional random sampling based on Krejcie and Morgan’s table. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS software. Entrepreneurial learning significantly enhances entrepreneurial intention, attitude, and innovative entrepreneurial behavior. Entrepreneurial attitude significantly predicts intention and innovative entrepreneurial behavior. Subjective norms significantly influence intention but do not directly affect innovative entrepreneurial behavior. Entrepreneurial intention significantly increases innovative entrepreneurial behavior. Indirect effects confirm that entrepreneurial learning and subjective norms positively shape innovative behavior through entrepreneurial attitude and intention. Strengthening entrepreneurial learning, attitude formation, and intention is essential for fostering innovative entrepreneurial behavior. The findings imply the need to expand entrepreneurship-based curricula, experiential learning environments, and innovation-oriented youth programs within higher education.